Eating disorders don't discriminate stories of illness, hope and recovery from diverse voices - Nwuba, Chukwuemeka; Spinn, Bailey (Philadephia Jessica Kingsley Publishers, 2024)
"This honest collection directly confronts stereotypes and misconceptions about what eating disorders look like and who they impact. Tapping into sources of expert knowledge throughout, the accounts showcase how you can begin to understand your own journey of body acceptance and recovery and support those struggling in silence"--
Keywords: Eating disorders -- Anecdotes; Eating disorders -- Patients -- Anecdotes